The Authority of Prosecutors in Handling Cases Involved by Children Who Commit Repeated Crimes - Larasati, Galuh; Suwondo, Denny (Jurnal Hukum Khaira Ummah, 2025)
Recidivist or Repeat Offender refers to a situation where a person commits multiple offenses or more after having been sentenced by a judge. When associated with children, the term "child recidivist" refers to a former juvenile inmate who, after being released from a correctional facility, commits a similar crime again, often referred to as a habitual offender. The purpose of this research is to identify and analyze the Prosecutor's Authority in handling cases involving children who commit repeat offenses, as well as to examine the challenges and solutions faced by prosecutors in dealing with such cases. This legal research is normative legal research, which focuses on studying legal norms or regulations. Normative legal research examines legal norms or regulations as a structured system related to a legal event. Prosecutors have broad authority in handling cases of children who commit repeat offenses, including determining the eligibility for diversion, prosecuting, and overseeing court rulings. The principle of restorative justice must be prioritized to ensure that children receive rehabilitation rather than mere punishment. Although diversion is not applicable to child recidivists, prosecutors must seek rehabilitative solutions that are not solely repressive. Challenges in handling such cases include regulatory limitations, lack of inter-agency coordination, insufficient rehabilitation facilities, and a shortage of experts. Solutions required include strengthening inter-agency coordination, enhancing rehabilitation facilities, and providing prosecutors with training in psychological and social approaches. Additionally, community involvement in community-based rehabilitation programs plays a crucial role in supporting the reintegration of children into society. With a balanced legal approach that prioritizes rehabilitation, children in conflict with the law can have a second chance and avoid reoffending.